2022
DOI: 10.3390/ma15155236
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Characteristics of Deep-Drawing Quality Steel Sheets in the Flat Die Strip Drawing Test

Abstract: Friction is one of the most important technological phenomena and has a large influence on the flow characteristics of a deformed material. A strip drawing friction test was used to evaluate the friction characteristics of 0.8 mm thick DC04 steel sheets in a sheet forming operation. Friction tests were carried out using a specially designed friction simulator and uniaxial tensile tests were carried out to determine the mechanical properties of the specimens. In addition, measurements of the sheet surface topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In [37], it was observed that friction under pressure lubrication conditions reduces the mean roughness of DC01 steel sheets by approximately 32%. Similarly, in [38], it was found that the Sa parameter of DC04 steel sheets increases with a reduction in normal pressure by approximately 12%-47%, in the range of contact pressures between 3 and 12 MPa. Most published works indicate a reduction in the surface roughness of sheet metal as a result of the surface flattening of asperities [39,40], or an increase in it as a result of the ploughing mechanism [41].…”
Section: Mlp For Prediction Of Roughness Parameter Samentioning
confidence: 74%
See 1 more Smart Citation
“…In [37], it was observed that friction under pressure lubrication conditions reduces the mean roughness of DC01 steel sheets by approximately 32%. Similarly, in [38], it was found that the Sa parameter of DC04 steel sheets increases with a reduction in normal pressure by approximately 12%-47%, in the range of contact pressures between 3 and 12 MPa. Most published works indicate a reduction in the surface roughness of sheet metal as a result of the surface flattening of asperities [39,40], or an increase in it as a result of the ploughing mechanism [41].…”
Section: Mlp For Prediction Of Roughness Parameter Samentioning
confidence: 74%
“…The increase in the pressure of the oil contained in closed lubricant pockets limits the mechanical interaction of the surface asperities and reduces friction by creating a pressure lubricant cushion [8]. The largest change in the Sku parameter occurs in conditions of a lack of pressurised lubrication and dry friction [38].…”
mentioning
confidence: 99%
“…Thus, stretch leveling with a controlled elongation value resulted in a favorable and stable stress state in the sheets. Szewczyk et al (2022) considered the frictional characteristics of deep drawing quality steel sheets in the flat die strip drawing test of 0.8 mm thick DC04 steel sheets [16]. They conducted friction tests under different pressure and lubrication conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Szewczyk et al [ 20 ] conducted friction testing using a specially designed friction simulator and performed uniaxial tensile tests to determine the mechanical properties of the specimens. In their study, they used commonly available oils as lubricants, which are relatively inexpensive compared to the specialized lubricants typically used in sheet metal forming for deep drawing processes.…”
Section: Introductionmentioning
confidence: 99%